Design and Build a Modern Parking Application Based on Android - Ilham Ilyas; Eko Junirianto; Annafi Franz (TEPIAN, 2021)
Parking is a non-moving condition of a vehicle that is not temporary. Problem associated parking di Samarinda is disparity between revenue targets with the realization of revenue from parking fees. The performance of roadside parking management is not optimal yet, where there are still many illegal parking officers. While their official parking attendants tend to be dishonest and do not hand over parking fee tickets to motorists , this study offers a solution that might solve the above problems by creating an android -based parking application made for parking attendants , this application is used by parking attendants to recorded all parked vehicles and stored directly on the web service . The Apps is made using Android Studio and Postman to test the API provided. The results of this study are expected to reduce the impact of disparities between revenue targets and revenue realization from parking fees.